Pelaksanaan Hak Kekayaan Intelektual Sebagai Objek Wakaf - Puji Sulistyaningsih; Heniyatun Heniyatun; Chrisna Bagus Edhita Praja; Dasep Nurjaman (JIPRO: Journal of Intellectual Property, 2019)
This study aims to determine the Islamic view of IPR as a waqf object, and procedures for implementing waqf with IPR objects. This study uses a normative juridical method with an approach to the Law and conceptual approach. The results showed that IPR was seen as one of the wealth rights (Huquq Maliyyah) in the view of Islam that received legal protection as other assets, so that IPR could be used as an object of waqf (al-mauqud 'alaih) both exchange contracts, commercial (Mu'awadhah ) and non-commercial contracts (tabarru'at). IPR as a waqf object is permitted by Islamic law as long as it fulfills the requirements as an object of waqf, as well as positive Indonesian law, this is reinforced by Law No. 41 of 2004 concerning Endowments; Government Regulation No. 42 of 2006; The decision of the Indonesian Ulema Council (MUI) No. 1 MUNAS / VII / 5/2005, allows IPR as an object of waqf. The HKI waqf procedure, in general, is not much different from the waqf procedure with objects of immovable objects such as land or other immovable objects but the difference is that there must be authentic evidence from the Directorate General of Islamic Education and the establishment of court states that the waqf object is not in dispute. Before the waqf pledge was made the Acting Actor of the Pledge of Endowments (PPAIW) consulted the Ministry of Religion in advance to get recommendations.